How ICT Investment and Human Development Accelerate Renewable Energy and Environmental Progress? - Hafeez, Muhammad; Gaudreault, Francis; Daud, Ali; Ben-Salha, Ousama (International Journal of Energy Economics and Policy, 2025)
Addressing environmental challenges relies on fostering pro-environmental behavior within society. Human development and ICT investment are crucial to comprehend their roles in promoting environmentally conscious actions. In this context, the present research investigates the relationship between human development, ICT investment, and pro-environmental behavior in the context of China. Employing a classy nonlinear NARDL model, the study explores the asymmetric impact of human development and ICT investment on pro-environmental behavior indicators. The results show that positive changes in human development and ICT investment promote renewable energy consumption and reduce CO2 emissions. In contrast, the negative change in the human development index does not significantly impact Renewable energy consumption, while it increases CO2 emissions. On the other hand, the negative change in ICT investment reduces renewable energy consumption and increases CO2 emissions. Policymakers should prioritize enhancing human development and encouraging sustainable ICT investment in China.